BIRTH AND MOTHERHOOD: CHILDBIRTH EXPERIENCE AND MOTHERS' PERCEPTIONS OF THEMSELVES AND THEIR BABIES. Issue 2 (20th February 2015) - Reisz, Samantha; Jacobvitz, Deborah; George, Carol
ABSTRACT Childbirth is a major experience in a woman's life, but the relation between childbirth experiences and later mother–infant outcomes has been understudied. This study examined the relation between mode of delivery and subjective birth experience (e.g., perception of control, social support during labor and delivery), and mothers' descriptions of their babies and their maternal self‐esteem, both powerful predictors of maternal caregiving behavior. This study had three questions: (a) Do mode of delivery and subjective birth experience predict mothers' descriptions of their babies and maternal self‐esteem? (b) Are the effects of mode of delivery on mothers' descriptions and maternal self‐esteem mediated by subjective birth experience? (c) Does infant age moderate any of these pathways? The sample consisted of 269 mothers of full‐term, healthy infants who gave birth in the year prior to the study. Mode of delivery showed a direct effect on how mothers describe their babies, but not maternal self‐esteem, which was not mediated by subjective birth experience. Subjective birth experience had direct effects on both outcomes. Infant age did not moderate any of these pathways. Results point to the subjective aspects of childbirth as important components of women's experience of labor and delivery. Implications are discussed.